2023
DOI: 10.3846/btp.2023.18505
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise Risk Management Disclosure and Ceo Characteristics: An Empirical Study of Go Public Companies in Indonesia

Rina Trisnawati,
Susilaningdyah Mustikawati,
Noer Sasongko

Abstract: Organizations can use enterprise risk management disclosures to share financial and non-financial risk information with external stakeholders. Chief Executive Officer (CEO) has a key role in enterprise risk management. This study examines the relationship between Indonesian CEOs’ characteristics and enterprise risk management disclosure. Purposive sampling is the basis for the process of gathering samples from the population. The research was conducted in 2020 and consisted of 475 non-financial Indonesian comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
2
2
0
Order By: Relevance
“…Findings align with those of previous studies that highlighted the importance of ERM and its implementation, given its holistic and integrated view of business risk (Anton e Nucu, 2020;Bromiley et al, 2015;Hernandez-Madrigal et al, 2020). The current study's analysis also demonstrated that respondents identified top management support and organisational climate as ERM implementation determinants, akin to existing literature (Otieno et al, 2019;Trisnawati, Mustikawati & Sasongko, 2023;Yahaya & Yakubu, 2022). Furthermore, most respondents linked ERM implementation to improved business performance; such results are in line with previous studies as well (Annamalah et al, 2018;Fakir & Jusoh, 2020;Fauzi et al, 2022;Florio & Leoni, 2017;Gordon, Loeb & Tseng, 2009;Jonek-Kowalska, 2019;Mahama et al, 2022;Lukianchuk, 2015;Rehman & Anwar, 2019;Muralidhar, 2010;Naseem et al, 2020;Nugraha, Rizal & Ganika, 2022;Perera et al, 2020;Rauf, Jabarand & Mansor, 2020;Yudianto et al, 2021).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Findings align with those of previous studies that highlighted the importance of ERM and its implementation, given its holistic and integrated view of business risk (Anton e Nucu, 2020;Bromiley et al, 2015;Hernandez-Madrigal et al, 2020). The current study's analysis also demonstrated that respondents identified top management support and organisational climate as ERM implementation determinants, akin to existing literature (Otieno et al, 2019;Trisnawati, Mustikawati & Sasongko, 2023;Yahaya & Yakubu, 2022). Furthermore, most respondents linked ERM implementation to improved business performance; such results are in line with previous studies as well (Annamalah et al, 2018;Fakir & Jusoh, 2020;Fauzi et al, 2022;Florio & Leoni, 2017;Gordon, Loeb & Tseng, 2009;Jonek-Kowalska, 2019;Mahama et al, 2022;Lukianchuk, 2015;Rehman & Anwar, 2019;Muralidhar, 2010;Naseem et al, 2020;Nugraha, Rizal & Ganika, 2022;Perera et al, 2020;Rauf, Jabarand & Mansor, 2020;Yudianto et al, 2021).…”
Section: Discussionsupporting
confidence: 77%
“…In terms of the relationship between respondents' demographic characteristics and their responses to commonly discussed ERM issues, the results of the present study are consistent with the findings of previous research. ERM issues were highly linked to respondents' educational level and job position; a finding confirmed by previous studies (Belas et al, 2023;Erin, Bamigboye & Arumona, 2020;Lamidi et al, 2022;Maharana et al, 2023;Odubuasi, Ofor & Ilechukwu, 2022;Otieno, Ogutu & Pokhariyal, 2019;Trisnawati, Mustikawati and Sasongko, 2023;Yahaya & Yakubu, 2022;Yang, Ishtiaq & Anwar, 2018).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Multinational companies must ensure that their financial strategies support innovation, investment in research and development (R&D), and market expansion. This is important to maintain a competitive advantage in a highly competitive market (Trisnawati et al, 2023). Thus, a strong financial strategy is not only the basis for a company's financial stability but also a key driver for long-term growth and sustainability.…”
Section: Financial Strengthening Strategies In Increasing Company Com...mentioning
confidence: 99%